The Significance of Teaching English for Specific Purposes in Costa Rica - Gamboa Agüero, Keilyn G.; Rodríguez Rodríguez, Scarleth P. (Revista Ensayos Pedagógicos, 2021)
This essay aims at analyzing the significance of the English for Specific Purposes (ESP) approach in Costa Rica. In addition, the authors scrutinized and compared different sources, such as journals, digital books, web pages, and others in order to provide relevant information regarding ESP, for instance, the aim of ESP based on its definition, its types, its objectives, and the effects of the absence of this approach in the learning process and the curriculum of the students as future employees, considering that Costa Rica does not have enough specialists in the area yet. Some programs to teach the target language for different majors need to be redesigned in order to guarantee the students a learning process based on the professional profile that they want to achieve, their needs, and their professional field. Likewise, this paper also explains the effects of the lack of ESP in the country. Hence, contemplating the effectiveness of making use of ESP to learn the target language can allow the education system of the country to take advantage of the benefits and opportunities that ESP represents for the nation.